Development of Indonesian Language Learning Modules Based on Local Wisdom to Enhance Appreciation of Literature - Widodo; Irma Novida; Muhammad Zulkifli; Nurul Setiani (INTERACTION: Jurnal Pendidikan Bahasa, 2025)
This study investigates the implementation of the Merdeka Curriculum in Indonesian language learning at junior high schools (SMP). The central issue identified is the gap between the government’s conceptual design of the curriculum and its actual classroom practice, which hinders the achievement of students’ literacy competencies. The objectives of the study are: (1) to analyze how the Merdeka Curriculum is implemented in Indonesian language subjects, (2) to identify the challenges faced by teachers and students, and (3) to describe stakeholders’ responses and adaptations to the policy. A descriptive qualitative approach with a case study design was employed. Data were collected through in-depth interviews with Indonesian language teachers, classroom observations in three junior high schools, and document analysis of lesson plans, syllabi, and curriculum guidelines. Data were analyzed using the Miles and Huberman model, which includes data reduction, display, and conclusion drawing, and the validity of findings was ensured through triangulation. The results indicate that while teachers have attempted to apply the principles of autonomy through project-based learning and authentic assessment, challenges remain, including limited resources, insufficient pedagogical readiness, and weak managerial support at the school level. Students demonstrated greater motivation and creativity in language tasks, yet continued to require structured guidance in organizing materials. The contribution of this study lies in providing concrete recommendations for developing teacher training modules, supplying contextualized teaching resources, and strengthening policy supervision. These recommendations are expected to enhance the effectiveness of the Merdeka Curriculum in improving Indonesian language competence at the junior high school level.